1982
DOI: 10.1524/ract.1982.31.34.139
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Studies of the Actinides: Stabilization of Americium(IV) in Aqueous Carbonate Solution

Abstract: The application of spectroelectrochemical techniques to the study of the actinide elements is described. Reticulated vitreous carbon, porous metal foam, and platinum screen optically transparent electrodes have been used for simultaneous generation and characterization of some less-stable oxidation states of americium.Stable 243 Am (IV) has been prepared by electrolytic oxidation of 243 Am(III) in various carbonate solutions including (NH 4 ) 2 C0 3 . Na 2 C0 3 , K 2 C0 3 , and Cs 2 C0 3 . Quantitative spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 16 publications
0
38
1
Order By: Relevance
“…The Np(VI) solution was diluted with water to adjust the Np(VI) concentration to approximately 0.1M. Reduction to Np(V) was completed using a conventional 3-electrode electrochemical system (Hobart et al 1982). The working electrode was a Pt-screen, the counter electrode a Pt-wire, and the reference electrode a saturated calomel.…”
Section: Methodsmentioning
confidence: 99%
“…The Np(VI) solution was diluted with water to adjust the Np(VI) concentration to approximately 0.1M. Reduction to Np(V) was completed using a conventional 3-electrode electrochemical system (Hobart et al 1982). The working electrode was a Pt-screen, the counter electrode a Pt-wire, and the reference electrode a saturated calomel.…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical syntheses of l70-labeled actinide solutions were performed using an EG&G PARR Model 173 potentiostatlcoulometer. Electrochemical cells used for bulk electrolysis had separate compartments for reference and counter-electrodes and are described in detail elsewhere (Hobart, Samhoun, et al 1982 nitrate complex dissipated and a green solution was collected. However, using this method, approximately 50% of the Np(IV) was oxidized to Np(V) by the HN03 and washed though the column.…”
Section: Methodsmentioning
confidence: 99%
“…The N p O solution was diluted with water to adjust the Np(VI) concentration to approximately 0.1M. Reduction to Np(V) was completed using a conventional 3-electrode electrochemical system (Hobart, Samhoun, et al 1982). The working electrode was a Pt-screen, the counter electrode was a Pt-wire, and the reference electrode was a saturated calomel.…”
Section: Methods Bmentioning
confidence: 99%
“…Each oxidized Am species is a potent oxidant in aqueous solution, spontaneously returning to the trivalent state in time, whether through the oxidation of water or more rapidly through interactions with any reducing species that might be present. The introduction of complexing agents, whether water soluble or lipophilic, impacts the relative stability of the oxidation states, most significantly stabilizing the species that are most strongly complexed, Am(IV) and Am(VI) [2][3][4][5][6][7][8][9][10][11][12] . We have previously demonstrated that the penta-and hexavalent oxidation states (Am(V/VI)) are considerably stabilized (though still capable of oxidizing water) in strongly basic solutions as well [13] .…”
Section: Project Narrativementioning
confidence: 99%
“…Distribution ratios for these systems are large. Previous IL/aqueous systems have focused on historical RTILs which have undergone extensive investigation such as bmimPF 6 and bmimBF 4 . Ligands used in these systems have been neutral oxo-donors (TBP) and β-diketones (HTTA).…”
Section: Task 2: Room Temperature Ionic Liquids (Rtils) As Media For mentioning
confidence: 99%